Effect of Arm Strength, Jump, and Height on Basketball Shooting Accuracy - Aris Mulyono; Priyanto; Cahyo Yuwono; Fery Darmanto; Dhika Panca Agustina; Muhammad Zihni Naim; Khoirul Anam (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of arm muscle strength, jump height, and height on the accuracy of basketball shots in students aged 12-15 years. The research problem arises from the gap between students' high enthusiasm for basketball and the inconsistent shooting results they achieve. This study uses a quantitative approach with a correlational design. The research subjects consisted of 34 male students from Public Middle School 22 Semarang who were selected randomly. The data collection involved physical fitness assessments, such as push-ups to measure arm muscle strength, vertical jumps to gauge jumping proficiency, height measurements with a stadiometer, and shooting tests utilizing a jump. Data analysis was performed using SPSS version 25, which included descriptive tests, prerequisite tests (normality and homogeneity), and multiple linear regression. The results showed a coefficient of determination (R²) of 0.147, indicating that the three variables collectively contributed only 14.7% to shooting ability. The ANOVA test yielded a significance value of 0.183, which is greater than 0.05, and the partial test also showed no significant effect from each independent variable. These findings suggest that shooting success in adolescents is more influenced by factors such as mastery of basic techniques, movement coordination, and training experience.